Modulation of apoptosis by sulforaphane is associated with PGC-1α stimulation and decreased oxidative stress in cardiac myoblasts - Fernandes, Rafael O. (2015)
Sulforaphane is a naturally occurring isothiocyanate capable of stimulating cellular antioxidant defenses and inducing phase 2 detoxifying enzymes, which can protect cells against oxidative damage. Oxidative stress and apoptosis are intimately involved in the pathophysiology of cardiac diseases. Although sulforaphane is known for its anticancer benefits, its role in cardiac cells is just emerging. The aim of the present study was to investigate whether sulforaphane can modulate oxidative stress, apoptosis, and correlate with PGC-1α, a transcriptional cofactor involved in energy metabolism. H9c2 cardiac myoblasts were incubated with R-sulforaphane 5 µmol/L for 24 h. Cell viability, ANP gene expression, oxidative stress and apoptosis markers, and protein expression of PGC-1α were studied. In cells treated with sulforaphane, cellular viability increased (12 %) and ANP gene expression decreased (46 %) compared to control cells. Moreover, sulforaphane induced a significant increase in superoxide dismutase (103 %), catalase (101 %), and glutathione S-transferase (72 %) activity, reduced reactive oxygen species levels (15 %) and lipid peroxidation (65 %), as well as stimulated the expression of the cytoprotective enzyme heme oxygenase-1 (4-fold). Sulforaphane also promoted an increase in the expression of the anti-apoptotic protein Bcl-2 (60 %), decreasing the Bax/Bcl-2 ratio. Active Caspase 3\7 and p-JNK/JNK were also reduced by sulforaphane, suggesting a reduction in apoptotic signaling. This was associated with an increased protein expression of PGC-1α (42 %). These results suggest that sulforaphane offers cytoprotection to cardiac cells by activating PGC1-α, reducing oxidative stress, and decreasing apoptosis signaling.